Pelayanan Birokrat Garis Depan (Street Level Bureucrat) Dalam Layanan Parkir Berlangganan di Kabupaten Jombang - Arine Octavia Anggraini; Tri Sulistyaningsih; Yana S Hijri (Departemen Ilmu Pemerintahan Fisip Unhas, 2020)
In Jombang, total vehicle transportation in 2018 is calculated from June. It reached 628,273 million units, including 578,855 million units of motorcycles, 34,931 million units of cars, 16,516 million units of freight cars, 920 bus units and 51 units of heavy equipment transportation. In addition, the number of vehicles registering subscription parking in Jombang district, two wheeled vehicles which registered subscription parking is 181,225 units, while four-wheeled vehicles are 17,493 units. From the statistical data shows that the Jombang community in its transportation needs every year has increased the government issued a regulation No.04 of 2017 for the sake of the creation of parking service needs. So far the problems faced in the subscription parking services in Jombang Regency are official carving services to users of subscription parking services that are not good or discretion occurs in the field. The research method used is descriptive qualitative to provide a description of street level bureaucrats in subscription parking services in Jombang. Data collection techniques are carried out through the process of observation, interviews and documentation. The theory used is the street level bureaucrat theory put forward by Michel Lipsky street level bureaucrat. The results show that subscription parking services in Jombang Regency are still not optimal due to several factors, namely first, the demand of the community continues to develop, secondly, the lack of understanding of official parking interpreters. Third, in the supervision system that is still lacking, the fourth attitude in making service to the community can still be said to be less than optimal, the fifth client relationship feels disadvantaged, the six transportation agencies do not have SOP as implementation management, the seventh development of complaints systems has no innovation, and the eight is low community participation.